(3QSGdI GdahGFO aj GdQCi GdeMUd ef GdCbOejf aj LhgQ GdCLQGe GdSeGhjI hHjGf ePgHge GdeMbb YfO GdeDdas - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3aUd bGdhG Cf GdCLSGe GdWHjYjI JfMUQ ai bSejf bSe eQcH hbSe HSjW hjYfhf HGdeQcH s
(3BNQgG (B:s
(3hcPdc ai aYd aYd hjTHg Cf jchf GdTYGYGJ MhGed ddbhi GdaGFVI hGddg CYde hCMce JeJ GdQSGdI HYhf Gdedc GdYdGe hYdi eMeO hBdg JeJ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
Keywords: (3GdcjejGA h GdWHjYjGJs